Florida Invader: Cane Toad - Steve A. Johnson; Monica E. McGarrity (EDIS)
Do you know how to tell the difference between a dangerous Cane Toad (a.k.a. “Bufo” Toad or Marine Toad) and a harmless native toad? This 2-page fact sheet will help you correctly identify and humanely euthanize this invasive toad that can kill pets. It was written by Steve Johnson and Monica McGarrity and published by the UF Department of Wildlife Ecology and Conservation, November 2010.